The Urgency of Understanding Learning Styles to Optimize Student Potential - Fuadi, Muhammad; Walidin, Warul; Salami, Salami (Innovative: Journal Of Social Science Research, 2024)
As an educator, understanding the characteristics and learning styles of students is a necessity before the learning process starts from planning, implementation and evaluation. Educators need to conduct diagnostic assessments to find out the initial data from the learning profile of students to help to achieve learning objectives. Learning style is a way for learners to learn according to their talents, interests, and what drives them to understand the subject matter more quickly. The learning style of students has its ways and methods so educators must understand to determine strategies, techniques and teaching media to optimize the potential of students. In general, there are three learning styles of students, namely, auditorium or the process of learning by hearing something is more dominant. Visual students learn by utilizing vision so that information is faster to understand—kinesthetic learning with actions, simulations and physical activity. An educator must consider the best learning method by looking at the characteristics of each individual with learning objectives and the development of student potential.